2019
DOI: 10.1111/jdv.15727
|View full text |Cite
|
Sign up to set email alerts
|

Nipple and areola lesions: review of dermoscopy and reflectance confocal microscopy features

Abstract: The differential diagnosis of nipple and areola complex (NAC) lesions encompasses a large spectrum of conditions from benign tumours to inflammatory diseases that could be challenging to recognize on clinical ground. While melanoma (MM) of the NAC is exceedingly rare, benign lesions are more frequent but could be difficult to distinguish from MM.Besides MM, other malignant tumours can affect this area and in particular Paget's disease (PD). For clinically doubtful lesions, biopsy is required, with possible fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…An uncommon type of breast cancer that appears similar to eczema on the breast or nipple 19. Occurs infrequently…”
Section: How Do You Diagnose the Cause Of Breast Or Nipple Pain?mentioning
confidence: 99%
“…An uncommon type of breast cancer that appears similar to eczema on the breast or nipple 19. Occurs infrequently…”
Section: How Do You Diagnose the Cause Of Breast Or Nipple Pain?mentioning
confidence: 99%
“…The characteristic features of eczema under RCM include cavernous degeneration, exocytosis, vesicle formation, and vasodilation (Astner, González, & Gonzalez, 2006). It was found that PD could be differentiated from eczema by the presence of dark Paget cells, which refer to PD, and the fact that spongiosis was more frequently found in eczema than in PD (Cinotti et al, 2019). In detail, eczema showed a regular honeycomb with blurred focus and multiple dark areas with clear border and fulfilled bright reflective particles.…”
Section: Discussionmentioning
confidence: 99%
“…surface, pink homogeneous surface, scales, red dots and small erosions. 8 It should be placed in the differential diagnoses of lesions which exhibit hyperkeratotic crusts along with arborizing vessels on dermoscopy.…”
Section: Declaration Of Patient Consentmentioning
confidence: 99%